Toward Sustainable Power Supply and Consumption of an Emerging Economy (Nigeria) - Okafor, Chukwuebuka Chukwujindu; Madu, Christian Ndubuisi; Ajaero, Charles Chimezie; Agomuo, Kingsley; Abu, Ezekiel (Journal of Economic Development, Environment and People, 2020)
Electricity supply offers significant and immense benefits to human society, and it is instrumental in driving economic growth, increased standard of living and technological developments. Its sustainable supply and consumption is related to many ecological discussions, and thus, present emphasis on renewable sources, such as solar and hydro. In Nigeria, however, challenges associated with electricity generation, transmission, distribution and consumption have not been adequately tackled. Poor electricity supply has adversely impacted the economy resulting to poor production, higher prices of goods and services, closure of industries, and loss of competitive advantage of Nigerian businesses. Conversely, energy-inefficient and non-conservation consumption behaviour of Nigerian electricity consumers contributes to the electricity demand - demand gap. Energy-efficiency and conservation is a sustainable tool for efficient power system. The paper show that the use of mostly post-paid and unmetered billing system is implicated in energy-inefficient consumption. The paper advocates for deployment of pre-paid meters to every electricity consumer; fiscal management, enforcement of energy saving policies such as use of compact fluorescent lamps (CFL); and emphasis on renewable energy (hydro and solar) sources, for electricity generation.